The Linguistic Turn in Contemporary Japanese Literary Studies Politics, Language, Textuality - Bourdaghs, Michael K. (Michigan Monograph Series in Japanese Studies, 2020)
The 1970s and 1980s saw a revolution in Japanese literary criticism. A new generation of scholars and critics, many of them veterans of 1960s political activism, arose in revolt against the largely positivistic methodologies that had hitherto dominated postwar literary studies. Creatively refashioning approaches taken from the field of linguistics, the new scholarship challenged orthodox interpretations, often introducing new methodologies in the process: structuralism, semiotics, and phenomenological linguistics, among others. The radical changes introduced then continue to reverberate today, shaping the way Japanese literature is studied both at home and abroad. The Linguistic Turn in Contemporary Japanese Literary Studies is the first critical study of this revolution to appear in English. It includes translations of landmark essays published in the 1970s and 1980s by such influential figures as Noguchi Takehiko, Kamei Hideo, Mitani Kuniaki, and Hirata Yumi. It also collects nine new essays that reflect critically on the emergence of linguistics-based literary criticism and theory in Japan, exploring both the novel possibilities such theory created and the shortcomings that could not be overcome. Scholars from a variety of disciplines and fields probe the political and intellectual implications of this transformation and explore the exciting new pathways it opened up for the study of modern Japanese literature.